Zinc monotherapy is effective in Wilson’s disease patients with mild liver disease diagnosed in childhood: a retrospective study - Ranucci, Giusy (Orphanet J Rare Dis, 2014)
BACKGROUND: Wilson’s disease (WD) evolves rapidly and is fatal if untreated. The treatment of WD patients with mild liver disease is not clearly defined. To address this issue, we evaluated long-term outcomes of three treatment regimens (D-penicillamine, zinc or both) in patients diagnosed in childhood. METHODS: We retrospectively evaluated efficacy, compliance and reasons for treatment discontinuation in 42 WD patients (median age at diagnosis: 6 years; median follow-up: 12 years) with mild liver disease. Treatment duration for each treatment block until a medication change or completion of follow-up was analyzed. Events of change of treatment were evaluated using Kaplan-Meier analysis. RESULTS: Total discontinuations due to treatment failure or adverse events were more frequent in patients receiving D-penicillamine (45%) or combination (36%) therapy than in patients receiving zinc (12%) (P = .001 and P = .02, respectively). Treatment failure was more frequent on D-penicillamine (28%) and combination therapy (36%) than on zinc (12%); the difference was statistically significant only between zinc and combination therapy (P = .03). First-line zinc monotherapy controlled WD-related liver disease in 13/15 patients (87%); the two subjects that failed on zinc were poor adherent. Zinc was effective in 3/5 (60%) patients that failed on D-penicillamine and combination regimens. All 15 D-penicillamine responders that switched to zinc had good control of liver disease at a median follow-up of 13.1 years. Among 6 D-penicillamine non-responders that switched to zinc, 4 (67%) responded. At follow-up completion, only 5/42 (12%) patients failed. Adverse event-induced discontinuation was significantly more frequent in patients on D-penicillamine than in patients receiving zinc (P = .03). CONCLUSIONS: Zinc monotherapy is effective in controlling WD-related liver disease both as first-line and as maintenance treatment in patients with mild liver disease diagnosed in childhood.